Bacterial analysis of semen and their antibiogram - RONALD, B S M; PRABHAKAR, T G (The Indian Journal of Animal Sciences, 2014)
The bacterial load in neat semen, diluted semen and frozen semen was assessed. Various organisms were isolated and identified up to their species level. Escherichia coli was the predominant organism isolated. Brucella abortus was isolated from semen samples. Antibiogram revealed that amikacin, chloramphenfcol and gentamicin were effective against isolated organisms. Pseudomonas species showed the highest resistance while Staphylococcus species were the most sensitive to the antibiotics tested. Most of the organisms were resistant to penicillin and streptomycin used in semen diluent.